Pair programming in inducing knowledge sharing - Md Rejab, Mawarny; Omar, Mazni; Ahmad, Mazida; Ahmad, Khairul Bariah (2011)
The Pair programming as a part of the Agile software development has been gaining acceptance among practitioners and software development community.This successful leads a wide use of pair programming in educational setting as pedagogy in programming course.Pair programming can foster knowledge sharing among students.Many studies have been done with pair programming in education however most of them do not highlight internalized knowledge particularly tacit knowledge from knowledge sharing processes between students who act as driver and navigator in pair programming practice.Thus, this paper will discuss knowledge internalization based on the knowledge sharing activities in pair programming practices by employing the process of Socialization, Externalization, Combination and Internalization (SECI).The sample of the study consisted of 60 students who were actively engaged in pair programming practices.The factors investigated were types of internalized tacit knowledge in the form of learning, thinking and decision making skills among the students. Online questionnaires were adapted from SECI model into educational context.T Test technique was used to analyze the data.This study is expected to contribute a better understanding of important knowledge sharing activities to construct student’s skills during Internalization process through pair programming.This study’s result will be considered for future rigorous theoretical framework for constructing tacit knowledge among the students in pair programming environment.